The Application of Tangram Media in Developing the Cognitive Skills of 4-5 Year Old Children at RA Takrimah - Helma, Helmawati; Andriansyah (UNIB Press, 2025)
Early childhood cognitive development encompasses thinking, remembering, imagining, and problem-solving, which require stimulation through learning media. This study aims to assess the effectiveness of tangram media in developing the cognitive abilities of children aged 4–5 years through exercises that involve identifying and arranging tangram shapes from basic geometric blocks to form new shapes. The observational results revealed that children aged 4-5 years have difficulties; their cognitive development remains limited. 16 of 22 children have not demonstrated the ability to arrange and name geometric blocks and to compare their similarities and differences. This study was conducted at RA Takrimah Banda Aceh. This study employed a quantitative pre-experimental design with a one-group pretest-posttest format. Purposive sampling was used, and of the 43 students in the population, 22 from class A2 were selected as the sample. Data collection methods include observation and documentation. Based on the results of the Normality Test, after ensuring that the data is normally distributed, the t-count value (19.439) > t-table (1.721) and sig (2-tailed) 0.001 < 0.05 obtained from the data analysis process indicate that the null hypothesis (Ho) is rejected and the hypothesis (Ha) is accepted. Based on the research findings, Tangram Media is a viable alternative to traditional methods for developing early childhood cognitive abilities.